Intraplate Late Jurassic deformation and exhumation in western central Argentina: Constraints from surface data and U–Pb detrital zircon ages - Naipauer, Maximiliano (2012)
Fil: Naipauer, Maximiliano. Universidad de Buenos Aires. FCEN. Departamento de Ciencias Geológicas. Instituto de Estudios Andinos “Don Pablo Groeber”. Buenos Aires, Argentina.